2005
DOI: 10.1002/clc.4960281106
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of continuous positive airway pressure treatment in obstructive sleep apnea syndrome using 24-hour urinary catecholamines

Abstract: SummaryBackground: Obstructive sleep apnea syndrome (OSAS) is related to diurnal sympathetic hyperactivity and increased blood pressure, both factors that are likely to lead to the development of cardiovascular disease.Hypothesis: The study investigated whether 24-h urinary catecholamines would reflect the effect of obstructive sleep apnea on autonomic activity.Methods: Standard polysomnography was performed in 17 patients with OSAS (age 53.7 ± 13.5 years, mean ± standard deviation). The number of apnea/hypopn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…Prospective studies also showed a strong association between AHI and THE increased arterial blood pressure [85]. It is relevant to note that the OSA-hypertension link is independent from other comorbidities like obesity [33,45,51,79,100]. Other study performed in OSA patients without hypertension, which were follow-up during five years for the risk of hypertension, concluded that there is a trend of association between AHI > 30 and the occurrence of the hypertension [75].…”
Section: Clinical Aspects Of Osamentioning
confidence: 98%
See 4 more Smart Citations
“…Prospective studies also showed a strong association between AHI and THE increased arterial blood pressure [85]. It is relevant to note that the OSA-hypertension link is independent from other comorbidities like obesity [33,45,51,79,100]. Other study performed in OSA patients without hypertension, which were follow-up during five years for the risk of hypertension, concluded that there is a trend of association between AHI > 30 and the occurrence of the hypertension [75].…”
Section: Clinical Aspects Of Osamentioning
confidence: 98%
“…Indeed, OSA patients show a positive relationship between AHI and the hypertension, which is independent of other risks [23,60,61,85,96,100,111,112]. Moreover, results obtained from the Wisconsin Sleep Cohort (an ongoing 21-years longitudinal study performed on 1500 Wisconsin state employees) have shown that untreated OSA patients have a high mortality risk associated with AHI [74,112].…”
Section: Pathogenic Mechanisms Of the Hypertension Induced By Osamentioning
confidence: 99%
See 3 more Smart Citations